Financial Performance Analysis Against Profitability Ratios at PT Astra Internasional Tbk - Mastia M Halimu; Liswan Rusman; Rosfianti M. Yadasang; Umar (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
The purpose of this study is to determine the financial performance of PT Astra International Tbk using the Profitability ratio, the data analysis techniques in this study are the Return On Asset (ROA) Ratio and the Return On Equity (ROE) Ratio, the data used is quantitative data and the data source in this study is secondary data obtained based on financial records for the last five years 2019-2023 at PT Astra International Tbk on the Indonesia Stock Exchange. The results of the study which were tested partially showed that return on assets had a fluctuating ratio each year, but the value of the return on assets ratio did not exceed the set industry value so that financial performance was declared unhealthy. The return on equity produced has the same value as the return on assets ratio, which is fluctuating and the industry value does not exceed the return on equity ratio value so that the financial performance of PT Astra International Tbk is not good.